Historia de la arquitectura argentina : desde sus origenes hasta la Torre Kavanagh - Galardi, Alberto; Alifano, Roberto ([Buenos Aires] : Diseño, 2017)
"This publication aims to illustrate the development and historical evolution of Argentine architecture from its origins in the River Plate to the construction of the emblematic Kavanagh Tower, erected in the city of Buenos Aires in 1936. The architecture that I set out to illustrate is symbolically concluded with the location in 1936, of the Kavanagh Tower, assumed as emblematic symbol of Buenos Aires, and a gap between architecture and two epochs between the extraordinary fact of an opulent and unrepeatable past already in the twilight of the powerful Argentine oligarchy and the arrival of Imposing economic, social and political changes of the Country" -- WORLDCAT.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2024. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Arquitectura -- Argentina -- Historia; Libros electrónicos.